Bilateral cmj assymetries in young male athletes: A study across different age groups and sports - Palazzi, D. A.; Yoo, S.-H.; Yoon, S.; Ryu, J.; Park, S.-K. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate bilateral countermovement jump asymmetries on a sample of 232 male student-athletes of 10 different sports, on a cross sectional approach over one year duration. Asymmetry in a number of force-related variables during the concentric and eccentric phases of a countermovement jump was defined as the absolute difference in performance between limbs expressed as a percentage of the total performance. Thresholds based on those asymmetries` means plus standard deviations of the whole sample were set. Our study indicates that regardless of the sport, asymmetries defined in this way are more likely to occur in active boys from 13 to 15 years old.